Serum paraoxonase 1 (PON1) activity in acute pancreatitis of dogs. (14th November 2014) - Tvarijonaviciute, A.; García‐Martínez, J. D.; Caldin, M.; Martínez‐Subiela, S.; Tecles, F.; Pastor, J.; Ceron, J. J.
<x xml:space="preserve">Abstract</x> OBJECTIVES Serum paraoxonase 1 is considered a marker of inflammation and oxidative damage. The aims of this study were to evaluate changes in serum paraoxonase 1 activity in dogs with acute pancreatitis, to correlate serum paraoxonase 1 activity and other analytes known to be altered in dogs with pancreatitis and to assess the relationship between serum paraoxonase 1 activity and disease severity in dogs with acute pancreatitis. MATERIALS AND METHODS Retrospective analysis of dogs with acute pancreatitis and healthy dogs in which serum paraoxonase 1 activity was measured were compared. RESULTS Median serum paraoxonase 1 activity was significantly lower in dogs with pancreatitis (n = 19) compared to healthy ones (n = 19). Serum paraoxonase 1 activity was negatively correlated with serum lipase and amylase activities, and C‐reactive protein and haptoglobin concentrations and was positively correlated with total cholesterol and glucose concentration. Disease severity was negatively correlated with serum paraoxonase 1 activity and positively correlated with triglyceride and C‐reactive protein concentration. CLINICAL SIGNIFICANCE Serum paraoxonase 1 activity is lower in dogs with acute pancreatitis and together with triglyceride and C‐reactive protein concentrations is a potential marker of disease severity.